ANALYSING COMMUNICATION COMPETENCE IN ORAL PRESENTATIONS: ENGINEERING STUDENTS’ EXPERIENCES - Yusoff, Mariana (Journal of Human Capital Development (JHCD), 2010)
With the rapid growth in science, technology, new organizations and management, industries critically need engineers who can communicate effectively with people from diverse backgrounds, to deal with multiple stakeholders, the government, private industries and the public at large. Studies have shown that although engineers may be technically sound, they are not effective communicators. This is particularly evident in the form of oral communication. Industries demand that graduating engineering students should be equipped with both technical and non-technical skills upon entering the job market as these skills are of vital importance in engineering workplaces. This constant emphasis on the need for good command of English in oral communication in graduating engineers has become a key concern in academia and the engineering profession. However, studies have shown that engineers and engineering students face communication problems, in particular, giving presentations at workplace, conferences, seminars, and in classrooms. Although there are abundant amount of various techniques, strategies, and skills in giving presentations provided in classroom teachings, articles, journals, literature, and on the Net; The question is why the communication problems particularly in giving presentations still linger. This paper describes the experience of Malaysian undergraduate engineers in giving presentation in the second language, English, during their 20-week internship program. It also describes understanding of the tasks assigned to them and presenting it to their supervisors. The combination of technical and non-technical knowledge is transferred and conveyed in a technical presentation. It is a representation of technical work-related matters, communication skills, students’ experience, namely their awareness, readiness and interaction with the non-threatening audience in the actual workplace settings. The study employs an ethnographic approach in gathering data. Data were collected through observations, participation and interviews. The data suggest that although the students are technically sound, they need to finetune their communication skills especially in oral and presentation skills, as these two are the desirable skills in the construction of an engineer. This set of skills is constantly highlighted as one of the biggest factors in determining a graduate’s success or failure. Keywords: oral presentation, communication skill, engineering education, industry